Kepemimpinan Kepala Sekolah Ditengah Pandemi COVID-19 pada Daerah yang Memiliki Hambatan Pembelajaran Jarak Jauh - sepfiawati Nurjannah (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2023)
This research was conducted to determine the leadership role of school principals amid the Covid-19 pandemic in areas that have distance learning barriers, this research was conducted using the literature review. From this study, it was found that the principal has a very important role to drive learning activities in schools. With the COVID-19 pandemic, which requires online learning, it is very difficult for schools in less developed areas. So that school principals must be able to make strategies for the smooth running of PJJ such as (1) students go to school by applying the health program to take assignments and materials that have been provided, (2) utilizing local radio stations, (3) implementing Blended Learning by forming small groups according to the location of the proximity of residence so that children who do not have gadget facilities can get a good education, (4) face-to-face learning approved by parents and the local government using the method shift and the application of strict health protocol with limited time for each meeting, bearing in mind that remote areas have a not too significant level of spread of Covid-19. The principal must be able to cope with learning loss that occurs as a result of the PJJ process that is not going well so that the role of the principal greatly determines the ongoing process of learning in schools